PENGOLAHAN NUGGET KOMPOSIT DENGAN BAHAN BAKU AMPAS TAHU DAN DAGING IKAN HIU - Wahyu Mushollaeni; Samsuri Tirtosastro (Universitas Tribhuwana Tunggadewi, 2007)
The aims of this research were to elucidate the best proportion of solid tofu’s waste and shark meats that produced composite nugget with better chemical, physical and organoleptical characteristics. Three treatments, i.e. nugget A (40% solid tofu’s wastes, 35% shark meats), B (50% solid tofu’s wastes, 25% shark meats), C (60% solid tofu’s wastes, 15% shark meats) were arranged in Completely Randomized Design with three replicates. Analysis factors were performed for water content, ash content, protein content, fat content, carbohydrate content, amino acid, calories and organoleptics (aromas and flavours). Results of this research showed that nugget composite type A posed the highest quality